David Chalmers’s Philosophy of Mind - Leonov, Andrii (Actual Problems of Mind, 2014)
The paper contains a detailed philosophical and translational analysis of the main notions of David Chalmers’s philosophy of mind as represented in his 1995 and 1996 program works.